Corrosion protection of mild steel by a new phosphonate inhibitor system in aqueous solution - M. Prabakaran; K. Vadivu; S. Ramesh; V. Periasamy (Egyptian Journal of Petroleum)
A protective film has been developed on the surface of the mild steel in low chloride aqueous environment using a synergistic mixture of an eco friendly inhibitor, imino dimethyl phosphonic acid (IDMPA) and Zn2+. The synergistic effect of IDMPA in controlling corrosion of the mild steel has been investigated by gravimetric and electrochemical studies in the presence of Zn2+. The formulation consisting of IDMPA and Zn2+ has excellent inhibition efficiency. The mixed mode of inhibition studied by potentiodynamic polarization and electrochemical impedance spectroscopy has shown that the changes in the impedance parameters like charge transfer resistance (Rct) and constant phase element (CPE) confirm the strong adsorption on the mild steel. Surface characterization inspection using Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDS) is used to ascertain the nature of the protective film. The mechanistic aspects of corrosion inhibition are proposed.